2019
DOI: 10.1016/j.isci.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic RNA Sensor Pathways and Nitazoxanide Broadly Inhibit Intracellular Mycobacterium tuberculosis Growth

Abstract: SummaryTo establish stable infection, Mycobacterium tuberculosis (MTb) must overcome host innate immune mechanisms, including those that sense pathogen-derived nucleic acids. Here, we show that the host cytosolic RNA sensing molecules RIG-I-like receptor (RLR) signaling proteins RIG-I and MDA5, their common adaptor protein MAVS, and the RNA-dependent kinase PKR each independently inhibit MTb growth in human cells. Furthermore, we show that MTb broadly stimulates RIG-I, MDA5, MAVS, and PKR gene expression and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 100 publications
(158 reference statements)
1
46
2
Order By: Relevance
“…This induction was observed only upon stimulation with live but not dead bacteria. Furthermore, it was shown that activation of RIG-I and MDA5 inhibited mycobacterial growth in different cell lines [60]. There is also evidence for a synergy of the DNA-recognizing cyclic GMP-AMP synthase (cGAS)/stimulator of interferon genes (STING)-axis with the MDA5-IRF7 pathway, activated by cytosolic RNA secreted from the endosome leading to IFNβ expression [61].…”
Section: Other Cytosolic Sensorsmentioning
confidence: 99%
See 4 more Smart Citations
“…This induction was observed only upon stimulation with live but not dead bacteria. Furthermore, it was shown that activation of RIG-I and MDA5 inhibited mycobacterial growth in different cell lines [60]. There is also evidence for a synergy of the DNA-recognizing cyclic GMP-AMP synthase (cGAS)/stimulator of interferon genes (STING)-axis with the MDA5-IRF7 pathway, activated by cytosolic RNA secreted from the endosome leading to IFNβ expression [61].…”
Section: Other Cytosolic Sensorsmentioning
confidence: 99%
“…The role of PKR, for which it was shown that sensing mycobacterial dsRNA leads to inhibition of translation, apoptosis, and ultimately decreased mycobacterial growth, is somewhat controversial as it has been recently questioned by retrospective investigation [65]: The observed difference between assumed KO mice in the PKR domain was attributed to different mice strains rather than to the impact of PKR itself. Nevertheless, recent cell line experiments could demonstrate that PKR activation by mycobacterial RNA leads to growth restriction in human cells [60].…”
Section: Other Cytosolic Sensorsmentioning
confidence: 99%
See 3 more Smart Citations